High Rates of Baseline Drug Resistance and Virologic Failure Among ART-naive HIV-infected Children in Mali. Issue 11 (November 2017) - Crowell, Claudia S.; Maiga, Almoustapha I.; Sylla, Mariam; Taiwo, Babafemi; Kone, Niaboula; Oron, Assaf P.; Murphy, Robert L.; Marcelin, Anne-Geneviève; Traore, Ban; Fofana, Djeneba B.; Peytavin, Gilles; Chadwick, Ellen G.
Abstract : Background: Limited data exist on drug resistance and antiretroviral treatment (ART) outcomes in HIV-1–infected children in West Africa. We determined the prevalence of baseline resistance and correlates of virologic failure (VF) in a cohort of ART-naive HIV-1–infected children <10 years of age initiating ART in Mali. Methods: Reverse transcriptase and protease genes were sequenced at baseline (before ART) and at 6 months. Resistance was defined according to the Stanford HIV Genotypic Resistance database. VF was defined as viral load ≥1000 copies/mL after 6 months of ART. Logistic regression was used to evaluate factors associated with VF or death >1 month after enrollment. Post hoc, antiretroviral concentrations were assayed on baseline samples of participants with baseline resistance. Results: One-hundred twenty children with a median age 2.6 years (interquartile range: 1.6–5.0) were included. Eighty-eight percent reported no prevention of mother-to-child transmission exposure. At baseline, 27 (23%), 4 (3%) and none had non-nucleoside reverse transcriptase inhibitor (NNRTI), nucleoside reverse transcriptase inhibitor or protease inhibitor resistance, respectively. Thirty-nine (33%) developed VF and 4 died >1 month post-ART initiation. In multivariable analyses, poor adherence [odds ratio (OR): 6.1, P = 0.001], baseline NNRTI resistance among children receiving NNRTI-based ART (OR: 22.9, P < 0.001) and protease inhibitor–based ART initiation among children without baseline NNRTI resistance (OR: 5.8, P = 0.018) were significantly associated with VF/death. Ten (38%) with baseline resistance had detectable levels of nevirapine or efavirenz at baseline; 7 were currently breastfeeding, but only 2 reported maternal antiretroviral use. Conclusions: Baseline NNRTI resistance was common in children without reported NNRTI exposure and was associated with increased risk of treatment failure. Detectable NNRTI concentrations were present despite few reports of maternal/infant antiretroviral use.